2008
DOI: 10.1080/00288230809510442
|View full text |Cite
|
Sign up to set email alerts
|

Improving the economic and environmental performance of a New Zealand hill country farm catchment: 1. Goal development and assessment of current performance

Abstract: A multi-stakeholder group including land managers, policy agencies and biophysical scientists was establishedto oversee a catchment scale project examining the economic and environmental performance of a representative North Island hill country catchment (296 ha Mangaotama catchment, Whatawhata) in the western Waikato region of New Zealand. The group first identified goals relevant to achieving a "well managed rural hill catchment", including viable businesses, healthy ecosystems, protected landscape values, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Catchment characteristics of soils, topography, vegetation, farming system, water quality and stream habitat are described in detail elsewhere (Quinn et al 1997a;Quinn & Stroud 2002;Dodd et al 2008b;Smale et al 2008). Briefly, the area is dominated by hilly to steep (17° to >30°) topography and yellowbrown soils on parent rock of sedimentary sandstones and siltstones (weathered greywacke and argillite).…”
Section: Study Area and Icm Changesmentioning
confidence: 99%
“…Catchment characteristics of soils, topography, vegetation, farming system, water quality and stream habitat are described in detail elsewhere (Quinn et al 1997a;Quinn & Stroud 2002;Dodd et al 2008b;Smale et al 2008). Briefly, the area is dominated by hilly to steep (17° to >30°) topography and yellowbrown soils on parent rock of sedimentary sandstones and siltstones (weathered greywacke and argillite).…”
Section: Study Area and Icm Changesmentioning
confidence: 99%
“…The CMG took the view that the essentially all-grass system in the catchment farm at the start of the project was not sustainable from either economic or environmental perspectives (Dodd et al 2008), and that vegetation change was the principle means of effecting change. Numerous other authors have suggested the need for increasing the level of tree cover in New Zealand hill land pastoral systems, dominantly in the context of erosion issues (eyles & Newsome 1992;Wall et al 1997;McGregor et al 1999;Cameron 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The second group of three scenarios involved a reduced pastoral area (128 ha) that was focused on the most favourable land within the catchment (to complement the 50% forestry scenario noted previously). These three scenarios used the same stock policies as the first three, with reduced numbers and assuming both greater average pasture production and a seasonal pattern of pasture production that better matched animal demand (given a higher proportion of lower land-use capability (LuC) class land; table 1 in Dodd et al 2008). These scenarios thus required a lower rate of nitrogen fertiliser supplementation, at 40 kg N ha -1 year-1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations